Demonstrating a decision support process for landscape conservation design - Thomas W. Bonnot; D. Todd Jones‐Farrand; Nate D. Muenks; Frank R. Thompson III (Wildlife Society Bulletin)
Abstract Despite the recent increase in landscape conservation and the design processes agencies are undertaking, there remains an implementation gap due to an inability to evaluate general strategies and account for uncertainties faced by managers. We demonstrated how a decision support process (DSP), recently developed to inform landscape conservation design, can address uncertainties and complexities inherent in landscape conservation to facilitate long‐term, large‐scale conservation planning. We applied the DSP to landscape conservation efforts within conservation opportunity areas (COA) of states in the Gulf Coastal Plains and Ozarks region. We engaged state planners within the region to identify important landscape conservation uncertainties they face in planning. We developed, simulated, and modeled the impacts of conservation addressing 3 uncertainties identified by state wildlife managers and evaluated the impacts by examining the responses of state and local populations of 2 bird species of conservation concern, prairie warbler (Setophaga discolor) and wood thrush (Hylocichla mustelina). The responses of prairie warbler populations to conservation strategies indicated that both approaches of protecting quality habitat from land‐use change and restoring and enhancing lower quality and nonhabitat improved their viability at regional, statewide, and COA scales. However, we noted that the relative effectiveness of strategies varied among states in ways that suggest a state's process for delineating COAs and what threats they face could influence which conservation approach to consider. Our findings highlight the need for regional coordination and the use of decision‐support processes to guide effective conservation at landscape scales.